Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.